THE RELATIONSHIP BETWEEN NURSES' KNOWLEDGE AND COMPLIANCE IN PERFORMING FALL RISK RE-ASSESSMENT - Sulistyowati, Arlina Dhian; Rusminingsih, Esri; Sari, Devi Permata; Kayati, Fitriana Noor; A, Yuli Widhi (Universitas Airlangga, 2022)
Introduction: The fall incidence will have a detrimental impact on the hospital, staffs and patients as the service recipients. This can be prevented by conducting fall risk reassessment. It is an assessment of patient's fall risk carried out by nurses. This study aims to determine the level of knowledge and compliance of nurses in carrying out a patient fall risk reassessment in the inpatient ward. Methods: This study used an observational analytical design with a quantitative method and a cross-sectional approach. A total sampling of 48 respondents were used as samples. Kendall Tau-b test was employed as the analysis technique. Results: The respondents were mostly female or as many as 33 people (68.8%). The educational level of the respondents was mostly D-III or as many as 32 people (66.7%). The majority of respondents' working period was 3-5 years or as many as 26 people (54.2 %). The average age of the respondents was 27.5 years, the respondents' knowledge was mostly good or as many as 24 people (50%), and the respondents' compliance in carrying out the fall risk reassessment was mostly compliant or as many as 41 people (85.4%). This study utilized the Kendall Tau-b test and obtained p value = 0.006 and Correlation Coefficient of 0.387. Conclusions: There is a significant relationship between nurses' knowledge of fall risk and their compliance in carrying out a fall risk reassessment in the inpatient ward of the PDHI Yogyakarta Islamic Hospital. The higher the knowledge, the higher the level of nurse compliance.